CALIDAD DEL SERVICIO AL CLIENTE EN EL HOTEL JARED DE LA PARROQUIA RICAURTE - Contreras Arce, Lorena Piedad (2018)
Hotel Jared is a hotel located in the parish of Ricaurte del Cantón Urdaneta. It emerged from the need to provide a lodging service for all those who wish to share pleasant moments. Later Mr. Don Eugenio Ninoska, an entrepreneur and business man, did a market research in 1986 and realized that in Ricaurte there was an abandoned niche, that is to say, there was no lodging service, so as a result of this study he decided to build a hotel of first category that covers the needs of users.